Multi-Object Attitude and Rate Tracking for Spacecraft in Formation Flying - Mohammad Abdelrahman, Mohammad Ibraheem (2011)

(untitled)
This paper presents the application of a Modified State–Dependent Riccati Equation MSDRE approach in multi-object attitude and rate tracking. A nonlinear controller using the MSDRE is developed through a pseudo-linearization of spacecraft augmented nonlinear absolute dynamics and kinematics. The developed controller is adopted to solve a trajectory tracking/ model following problem. Based on the same approach the relative dynamics and kinematics are augmented to the previous system to represent the overall system process model. The developed controller is applied to spacecraft in formation as a decentralized control algorithm which aims to track absolute and relative attitude and rates simultaneously.The developed controller is applied to a spacecraft formation in a remote sensing mission.The simulations results show the capabilities of the MSDRE to handle the multi-object tracking without any unnecessary control efforts that might lead to actuators saturations or additional control logic to switch between absolute and relative tracking. Finally the stability of the controller is verified using Lyapunov function method.